Shading by marine litter impairs the health of the two Indo-Pacific scleractinian corals Porites rus and Pavona cactus. (September 2020) - Mueller, Jasmin S.; Schupp, Peter J.
Abstract: Marine litter is recognized as one factor affecting coral health. It causes shading, bleaching, physical damage, necrosis, and mortality. This study provides the first evidence that direct contact by plastic and cotton affects coral health within 60 days. In a controlled aquarium experiment, two common Indo-Pacific scleractinian corals, Porites rus and Pavona cactus, were shaded for 60 days by transparent plastic (polypropylene, PP), dark plastic (PP) and cotton. Cotton disintegrated completely after 30 to 42 days, allowing the corals to recover. Transparent plastic became opaque over time due to microfouling, resulting in bleaching of the affected coral parts. Dark plastic had the strongest effect, including bleaching, necrosis and reduced growth within 60 days. Moreover, the two coral species responded differently to the treatments. This is the first report demonstrating that plastic and cotton litter can affect coral health and even cause partial mortality within 60 days. Highlights: The extent of shading effects by marine litter are material- and coral species-specific. Direct contact by plastic and cotton affects coral health within 60 days. Cotton has less effect than plastic materials by disintegrating completely within 30 to 42 days, allowing the corals to recover. Dark-colored plastic suppresses coral growth and induces rapid bleaching resulting in partial mortality within 60 days.